Unbuttoning the Ancestral Flower of Angiosperms. (July 2018) - De-Paula, Orlando C.; Assis, Leandro C.S.; Ronse de Craene, Louis P.
Abstract : A recent study using an extensive data set plus sophisticated analytical tools reconstructed a model of the ancestral angiosperm flower. Although attractive, it presents problems of homology assessment. We discuss its inconsistencies and endorse the use of a comparative model that integrates biological parameters as essential to elucidate floral evolution.